Encapsulated carboxylic acid dimers with compressed hydrogen bonds - Ajami, Dariush; Tolstoy, Peter M.; Dube, Henry; Odermatt, Severin; Koeppe, Benjamin; Guo, Jing; Limbach, Hans-Heinrich; Rebek, Julius (Angewandte Chemie International Edition, 2011)
Under pressure: Carboxylic acid dimers enclosed in molecular capsules experience an internal pressure of about 5-10-kbar, which leads to compression of the hydrogen bonds (see scheme). © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-04-02
Keywords: carboxylic acid dimers; host-guest systems; hydrogen bonds; NMR spectroscopy; self-assembled capsules